Penggunaan Kitab Sisilah At-Ta’lim Al-Lughoh Al-Arabiyyah Annahwi Mustawa Tsani Pada Pembelajaran Nahwu Di Ma’had Umar Bin Khattab Universitas Muhammadiyah Sidoarjo - abyanrf; Najih Anwar (Jurnal Naskhi Jurnal Kajian Pendidikan dan Bahasa Arab, 2025)
This research aims to determine the use of the Kitab Sisilah at-Ta’lim al-Lughoh al-Arabiyyah Annahwi Mustawa Tsani in Nahwu learning at Ma’had Umar Bin Khattab (MUBK) Muhammadiyah University of Sidoarjo. The research uses a descriptive qualitative approach with data collection methods in the form of interviews, observations, and documentation. The research subjects include lecturers and second-year students. The research results show that learning is conducted through three main stages: (1) initial agreement, where the lecturer emphasizes the importance of attendance to ensure a thorough understanding of the material; (2) the learning process, which consists of the explanation of nahwu rules, tadribat exercises, and material reinforcement at the end of the session; and (3) evaluation, which is conducted through tadribat discussions, Midterm Exams (UTS), and Final Exams (UAS). The learning strategy implemented prioritizes time efficiency by focusing on rules and exercises, while reading the text is only done if there is extra time. Factors supporting the success of learning include the consistent attendance of students and lecturers, a conducive learning environment, and systematic and clear teaching methods. However, this success can be hindered by the absence of students or lecturers, which disrupts the continuity of learning